(untitled) (Journal of Asian Development Studies, 2024)
This research paper aims to assess China’s Strategic and economic interests in Balochistan: The role of natural resources and geopolitical implication of Gwadar Port in the Belt and Road Initiative (BRI). The paper seeks to determine whether Balochistan’s resource endowment in copper, gold, and natural gas is central to Chinese investments or if there are other factors, such as the location of the Gwadar port. The study explores China’s geopolitical and economic structures and unpicks the impact of Chinese infrastructure investments on local and global systems. The positive results imply that although natural resources are essential, the location as a strategic trade and energy corridor of Gwadar Port is the primary pull factor for China to the region.